Comparative Analysis of Ankle-Brachial Index in Chronic Myeloid Leukemia Patients Treated with Imatinib versus Nilotinib at Adam Malik Hospital - Alfajri, Muhammad Jailani Alfajri; Syahrini Lubis, Henni; Gatot, Dairion (CoinReads Media Prima, 2025)
Introduction: Chronic myeloid leukemia (CML) is commonly managed with tyrosine kinase inhibitors (TKIs) such as imatinib and nilotinib. However, these therapies are associated with cardiovascular risks, including peripheral arterial disease (PAD). This study compares the Ankle-Brachial Index (ABI), a non-invasive measure of PAD, in CML patients receiving imatinib or nilotinib at Adam Malik Hospital, Medan. Methods: A cross-sectional study was conducted from December 2023 to February 2024 at Adam Malik Hospital. Forty-eight CML patients (34 on imatinib, 14 on nilotinib) were enrolled using consecutive sampling. ABI was measured to assess PAD prevalence, with values <0.9 indicating abnormality. Data were analyzed using independent t-tests and chi-square tests, with significance set at p<0.05. Results: The mean age was 42.9 years (imatinib) and 49.1 years (nilotinib). Abnormal ABI values were observed in 20.6% (7/34) of imatinib-treated patients and 50% (7/14) of nilotinib-treated patients. The mean ABI for the left leg was significantly lower in the nilotinib group (0.91 ± 0.12) compared to the imatinib group (1.06 ± 0.11, p=0.017). A significant difference in ABI values between groups was confirmed (p=0.042, odds ratio 3.857), indicating a higher PAD risk with nilotinib. Conclusion: Nilotinib therapy is associated with a higher incidence of PAD compared to imatinib in CML patients. These findings underscore the need for routine cardiovascular monitoring in TKI-treated patients and further research into the vascular effects of TKIs.